2014
DOI: 10.1097/imi.0000000000000052
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sex on the Risk to Develop Contrast-Induced Nephropathy after Transcatheter Aortic Valve Implantation

Abstract: Objective Contrast-induced nephropathy (CIN) is the third most common cause of acute renal failure and is associated with increased morbidity and in-hospital mortality. Some recent studies identified female sex as a risk factor of CIN. The aim of this study was to determine the relative impact of female sex on the development and clinical outcome of CIN in patients with preexisting renal impairment after transapical transcatheter aortic valve implantation (TAVI). Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…An advantage of RT3D-TEE is that it can be performed at the bedside or directly before or even after prosthetic valve implantation for the evaluation of the implanted prosthesis, e.g., for identifying paravalvular regurgitation. Moreover, it is a good alternative to MDCT, particularly when it is essential to decrease the burden of contrast agent administration as in patients with compromised renal function—thereby potentially reducing the incidence of acute kidney failure [ 40 ] —as well as in patients with cardiac arrhythmia. RT3D-TEE may be performed immediately before and after procedures in the hybrid operating room [ 37 •, 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…An advantage of RT3D-TEE is that it can be performed at the bedside or directly before or even after prosthetic valve implantation for the evaluation of the implanted prosthesis, e.g., for identifying paravalvular regurgitation. Moreover, it is a good alternative to MDCT, particularly when it is essential to decrease the burden of contrast agent administration as in patients with compromised renal function—thereby potentially reducing the incidence of acute kidney failure [ 40 ] —as well as in patients with cardiac arrhythmia. RT3D-TEE may be performed immediately before and after procedures in the hybrid operating room [ 37 •, 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The features of the included studies are shown in Tables 1 , 2 (Ref. [ 10 , 11 , 13 , 14 , 15 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]). Due to the large number of articles included and the large sample size, some trials lacked the baseline data of some men and women.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that calculating the ratio of CM volume /GFR ratio might be helpful in preventing kidney injury: a ratio of 3.9 was specified to predict kidney injury with 71% sensitivity and 80% specificity [62]. Other authors observed a possible association between a higher incidence of AKI and 30-day mortality with regard to the extensive use of CM during TAVI among high-risk patients with preexisting renal impairment [33,63]. This is in line with findings of a study in 270 TAVI patients, showing that postoperative AKI depend on the amount of contrast agent used intra-interventionally.…”
Section: A U T H O R Accepted Manuscriptmentioning
confidence: 99%